Development of anti-drug antibodies is associated with shortened survival in patients with metastatic melanoma treated with ipilimumab. (4th May 2018) - Kverneland, Anders H.; Enevold, Christian; Donia, Marco; Bastholt, Lars; Svane, Inge Marie; Nielsen, Claus H.
ABSTRACT: Introduction: Checkpoint inhibitors, including the CTLA-4 blocking antibody ipilimumab, have become the new standard therapy for many metastatic cancers. Development of anti-drug antibodies (ADAs) after treatment with other biopharmaceuticals has been thoroughly described, but the induction of ADAs after treatment with checkpoint inhibitors has been inadequately investigated. In this retrospective study, we relate ipilimumab serum levels and anti-ipilimumab antibody levels to clinical outcomes in patients with metastatic melanoma (MM). Method: Serum samples from 31 patients with MM were analyzed for serum levels of ipilimumab and ADAs to ipilimumab at baseline, and before the 2 nd and 4 th infusion using an in-house bead-based assay. The results were correlated with progression-free survival (PFS) and overall survival (OS). Results: Low serum levels of ipilimumab before the 2 nd infusion correlated significantly with a shorter OS (p = 0.01) and PFS (p = 0.02). Eight patients (26%) were ADA-positive at either timepoint. ADA positivity correlated significantly with a shorter OS (p = 0.03) with a hazard ratio (HR) of 3.0 (95% CI: 1.2-7.8). Four of 8 ADA-positive patients (50%) discontinued therapy before the 4 th infusion due to disease progression, compared to three of 23 (13%) ADA-negative patients. Conclusion: We confirm that low serum levels of ipilimumab are associated with a shortened OS, and we show for the first time that ADAs to ipilimumab are associated with shorter OS in patients with MM.